Evaluation of Nutritional and Technological Attributes of Whole Wheat Based Bread Fortified with Chia Flour - Bouchra Sayed-Ahmad; Thierry Talou; Evita Straumite; Martins Sabovics; Zanda Kruma; Zeinab Saad; Akram Hijazi; Othmane Merah (Foods, 2018)
The aim of this study was to investigate and compare the effect of wheat bread fortification with varied levels (2%, 4%, and 6%) of chia seed powder (full fat) and cakes (defatted, residue after oil extraction). Chia flour was added to whole wheat bread rich in vital wheat gluten for the first time. The breadcrumbs were assessed for their antioxidant activity, nutritional content, textural properties, color, and sensory profiles. The addition of chia seed powder, particularly in high levels, was more effective in improving antioxidant activity compared to bread fortified with chia cakes. Bread supplementation with chia flour improves its nutritional value, especially in the case of chia cakes. A higher moisture content and lower hardness were observed after bread fortification, the influence was more evident with the defatted cake than with seed powder. Fortification with chia flour led to darker breads without significantly affecting their global acceptability. However, the fortified bread showed better values than control in terms of sensory profile. These results suggest that the addition of chia seed powder and defatted cake can enhance the overall whole wheat bread quality. Our results also highlight that bread making could be an unconventional alternative for the exploitation of defatted chia seed.